Effect of methanol extract of Dicranopteris linearis leaves against paracetamol- and carbon tetrachloride (CCl4)-induced liver toxicity in rats - Mamat, Siti Syariah; Kamisan, Farah Hidayah; Wan Zainulddin, Wan Noraziemah; Ismail, Noor Aisyah; Yahya, Farhana; Din, Siti Shamsahal; Zabidi, Zalina; Mohtarrudin, Norhafizah; Abd. Kadir, Arifah; Zakaria, Zainul Amiruddin (Academic Journals, 2013)
The present study aimed to determine the hepatoprotective activity of methanol extract of Dicranopteris linearis leaves (MEDL) using two models of liver injury in r ats. Rats (n = 6) received 10% DMSO(negative control), 200 mg/kg silymarin (positive control) or MEDL (50, 250, and 500 mg/kg) orally once daily for 7 days and 3 hours after the last adminis tration of the test solutions, they were subjected to the hepatotoxic induction either using carbon tetrachloride (CCl4) or paracetamol (PCM). The bloods and livers were collected and subjected to biochemical and microscopical analysis. From the data obtained, all doses of MEDL significantly (P < 0.05) reduced the alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels in CCl4-induced hepatotoxic rats while only the 500 mg/kg MEDL caused significant (P < 0.05) reduction in the level of both enzymes in the PCM-induced liver toxicity model. The histological results obtained were in line with the biochemical analysis. In conclusion, the MEDL-induced hepatoprotective activity is attributed partly to its free radicals scavenging and antioxidant activities and high flav onoids content.